PROBLEMS REGARDING THE DETERMINATION OF LOSS OF PROFIT CAUSED BY UNLAWFUL USE OF A TRADE SECRET - Kontrimas, Vaidas (Teisė, 2017)
The person having sustained damages through unfair competition actions upon disclosure and use of the other entity’s trade secret (hereinafter – unfair competition actions) has a right to seek a court order for compensation of loss of profit. Taking into account the specific features of unfair competition actions, determination of damages caused by unfair competition actions is becoming one of the most important and complicated aspects in this type of proceedings. In the light of the above, this article deals with the currently-established criteria for determining loss of profit caused by unfair competition actions. The article looks at the sufficiency of such criteria for determining an objective and fair amount of damages to be compensated. The article also indicates additional criteria that could be used in determining loss of profit caused by unfair competition actions. Using such additional criteria should be considered particularly important for determining a more objective and fair amount of damages corresponding to the specific features of unfair competition actions.